The effect of somatosensory input on motor imagery depends upon motor imagery capability - Mizuguchi, Nobuaki; Yamagishi, Takahiro; Nakata, Hiroki; Kanosue, Kazuyuki (Frontiers in Psychology, 2015)
We investigated that the relationship between motor imagery ability and the effect of tactile input associated with holding a tennis racket on motor imagery of the forehand and backhand swings. The effect was assessed by the time utilized for motor imagery (mental chronometry). Seventeen tennis players imagined forehand and backhand swings with a forehand grip, a backhand grip or while holding nothing. In all cases, imaging the swings took longer than the time taken for a real swing. For imagery of the backhand swing, holding a racket with a backhand grip decreased the imaging time (p < 0.05) as compared to the trials with a forehand grip or while holding nothing. On the other hand, holding the racket with a backhand grip tended to increase the time required for forehand swing imagery. These results suggest that a congruent grip improves, and an incongruent grip deteriorates, motor imagery of the backhand swing. For players who took a longer time in the condition where they held nothing (i.e. poor imaging ability), the effect of a congruent backhand grip was greater (r = 0.67, p<0.01). However, a congruent forehand grip did not improve motor imagery of the forehand swing. Since 15 of the participants in the present study favored the forehand swing compared to the backhand swing, the participants would have been more familiar with the forehand swing. Thus it would have been easy to vividly imagine the (familiar) forehand swing even when they were not holding a racket. We speculate that tactile input associated with holding a tool improves a vividness of motor imagery of a less familiar movement, especially for those who have poor imaging ability. In the future, it will be important to clarify whether the effect of tactile input associated with holding a tool is dependent upon movement familiarity/performance level.